APPLICATION OF LEXICOGRAPHIC METHODS IN FINDING NEW SOLUTIONS FOR THE CONSTRUCTION OF SWITCH FAUCETS - VLAD ANDREI CIUBOTARIU; IONEL OLARU; CRINA MARIA RADU; COSMIN GRIGORAS (Journal of Engineering Studies and Research, 2021)
Methods and techniques to stimulate creativity are indispensable in the process of obtaining more reliable and competitive products. For the elaboration and efficient use of logical-deductive methods and techniques in creativity, it is necessary to know a minimum of combinatorics, which include arrangements, combinations, permutations, graphs and finite networks. From the multitude of methods of orderly enumeration of all ensembles, without omissions or repetitions, the lexicographic method is recommended, according to which, the assemblies are ordered in ascending order according to the sum of the component elements index. The main purpose of this paper is to apply the lexicographic method to obtain a more efficient flow faucet body in terms of working fluid behavior. Thus, the pressure, flow, velocity variation and degree of fluid vorticity have better values for the faucet body obtained by applying the lexicographic method. Therefore, by applying the flow simulation method, it was possible to characterize the behavior of the working fluid.